Infiltração, retenção e disponibilidade de água em solos pedregosos - Fachi, Suélen Matiasso (2024)
The knowledge of soil water functions, such as infiltration, retention, and water availability, is essential for plant development and agricultural practices. However, in stony soils, the influence of coarse fragments (Ø >2 mm) on these functions is not fully understood. This thesis aims to evaluate whether coarse fragments affect water infiltration, retention, and availability in stony soils. The thesis is divided into three articles. In the first article, the hypothesis that an increase in the presence of coarse fragments in the soil profile enhances infiltration rate was tested. Infiltration tests were conducted at three sites with different amounts of coarse fragments. The results supported the hypothesis, showing that the infiltration rate can be up to sixteen times higher in profiles with at least 60% coarse fragments. Based on these results, we suggest that susceptibility to water degradation is not a universal characteristic of all stony soils. In fact, some of these soils may be less prone to degradation caused by water erosion than previously believed. The second article aimed to evaluate whether the retention of available water in coarse fragments and its release to the surrounding fine soil depend on the size and porosity of the coarse fragments. Three experiments were conducted, assessing coarse fragments of different sizes and porosities. In the first experiment, the release of water from coarse fragments to the fine soil was evaluated in a bed consisting of a mixture of fragments and fine soil with evaporation. In the second experiment, water retention and availability were assessed in the fragments. In the third experiment, the release of available water from coarse fragments to the fine soil in pots with plants was evaluated. The porosity of coarse fragments has a significant impact on the retention and release of available water, while the effect of fragment size is relatively minor. The objective of the third article was to assess whether describing water retention in stony soils requires a bimodal function and to test hydraulic parameters in the Hydrus-1D model in drainage experiments. Field drainage experiments were conducted in stony soil profiles with different amounts of coarse fragments. Water content and matric potential were monitored at different soil depths during drainage experiments, field evaporation, and laboratory evaporation using a soil water potential device. The use of the bimodal Van Genuchten-Mualem retention function was evaluated using the curve-fitting software RETC. Subsequently, hydraulic parameters were tested and, when necessary, optimized in Hydrus-1D to simulate drainage. The need for a bimodal water retention curve to describe water retention in stony soils was confirmed. The methodology used in this study was essential for identifying the bimodal water retention curve. The adjusted parameters were consistent and allowed for drainage simulation in Hydrus-1D. This validates the methodology used in this study to determine the bimodal water retention curve and highlights its practical applicability.